Estimación de la abundancia de Lagidium peruanum “vizcacha” (Meyen, 1883) basado en conteos indirectos en el ACP Lomas del Cerro Campana. Trujillo, Marzo – Junio, 2017. - Acedo Zegarra, Victor John (2017)
The present investigation determined the abundance of Lagidium peruanum "vizcacha" (Meyen, 1883), from March to June of 2017, in the Private Conservation Area “Lomas del Cerro Campana”, in the city of Trujillo (District of Trujillo - La Libertad Department) , Settled on the desiccated-Subtropical (dd-S) desert, formed of a wavy, sandy base with some rocky-rocky ravines. For the abundance of L. peruanum, the caves or burrows were inventoried in 7 georeferenced transects in the ACP leeward sector, with which a simple linear regression analysis was projected for the total area of the ACP. In each of the positive caves or burrows, the proportion of excreta and excreta size were evaluated to determine the number of L. peruanum individuals present. The minimum and maximum abundance estimated in the total area of the ACP is 4,870 ind. (1066 ind / ha) (r = 0.967), and 6,852 ind. (1,501 ind / ha.) (R = 0.972), respectively, as well as the abundance of the estimated adult and juvenile population, was 3,780 ind. (0.828 ind / ha.) (R = 0.976), and from 3 073 ind. (0.673 ind / ha.) (R = 0.965), respectively, and has a uniform spatial distribution (A = 0.93), according to the Hopkins and Skellam index; in the ACP “Lomas del Cerro Campana”, during the months of March to June of 2017.